Development of existing and novel tyrosinase inhibitors for skin pigmentation: intradermal delivery, biological evaluation and mechanistic studies - Li, Zhiwei (2023)
Hyperpigmentation is a common skin disorder caused by the abnormal production and accumulation of melanin, including sunspots, post-inflammatory hyperpigmentation, and melasma. Melanin is produced by melanocytes in melanosomes through a complex process called melanogenesis, in which tyrosinase plays a critical role. Therefore, exploration of the permeation capacity, biological activity, and metabolic mechanisms of existing and novel tyrosinase inhibitors is necessary and will help to improve the problem of hyperpigmentation. One of the main problems regarding the existing tyrosinase inhibitor, Alpha-Arbutin, is its poor permeation ability. In this thesis, it is proposed that the ability of the drug to permeate within the skin can be enhanced by solid microneedles and dissolving polymeric microneedles. It was found that both solid microneedle post-treatment and dissolving polymeric microneedles were able to facilitate the intradermal penetration of Alpha-Arbutin. Interestingly, the soluble polymeric microneedle was able to reach deeper into the skin, targeting delivery to the basal layer, making it a more desirable option. Also, given the compliance and safety issues associated with solid microneedles, dissolving polymeric microneedles overall have better prospects. Although we found that the use of dissolving polymeric microneedles is an effective way to improve the permeation of Alpha-Arbutin, there still exists a need to develop a novel compound with strong tyrosinase inhibition and optimal partition coefficient. Thus, in this thesis, we have identified the new compound 11c as a promising tyrosinase inhibitor with excellent anti-tyrosinase activity shown in melanoma cells A375. Compound 11c is hydrophobic and demonstrated good in vitro and in vivo penetration ability. Most importantly, compound 11c was able to successfully improve UV-induced skin pigmentation in guinea pigs in the in vivo experiments. All suggest that compound 11c may serve as a promising and effective novel tyrosinase inhibitor that could be used to develop potential therapies for the treatment of skin hyperpigmentation. After having evaluated the biological activity as well as the physicochemical properties of 11c, we turned our attention to its mechanism of action. In this thesis, the metabolic pathway of tyrosinase modulators in melanoma cells was investigated. A combination of LC-MS targeted metabolomics and OrbiSIMS analysis was used to investigate the differences in metabolites in melanoma cells from different experimental groups. It was found that disorders of Malate-Aspartate Shuttle and fatty acids were associated with the role of tyrosinase modulators in melanoma cells. This suggests that fatty acids and respiration have important functions in melanoma cells. This also provides a strong contribution to subsequent scholars searching for new therapeutic targets for pigmentation and melanoma.